O sofrimento da razão na neurose obsessiva - Ferraz, Gabriel Domingues (Universidade Federal de São Carlos, 2024)
Obsessive neurosis is a condition in which individuals experience intrusive and unwanted thoughts, known as obsessions, that generate significant anxiety and discomfort. In some cases, to alleviate this anxiety, they perform repetitive, ritualized behaviors called compulsions. However, these compulsions are usually not pleasurable in themselves, but are performed as an attempt to neutralize or avoid the obsessions and reduce associated anxiety. Based on clinical observations, Freud considered defense as the nuclear point in the psychic mechanism of neuroses, closely linking this clinical picture with the dimension of thought. Among the most striking aspects, there is the predominance of reason, lack of affection and a severe ethical sensitivity. This monograph aims to understand how the clinical fact of the predominance of the sphere of thought over affective life in obsessional neurosis is described, and how this phenomenon is linked to the psychic dynamics of the obsessive subject. With this, we seek to identify how excessive intellectualization can harm analytical treatment, and how the technique should be modified in order to deal with this phenomenon.
The suffering of reason in obsessional neurosis
Keywords: Psicanálise; Teoria freudiana; Transtorno obsessivo-compulsivo; CIENCIAS HUMANAS::PSICOLOGIA::TRATAMENTO E PREVENCAO PSICOLOGICA